Utilization of organic phosphorus sources by oilseed rape, sunflower, and soybean - Belinque, Hernan (2015)
We evaluated the ability of Brassica napus L. (oilseed rape), Helianthus annus L. (sunflower), and Glycine max L. (soybean) plants grown inoculated with or without bacteria to utilize organic P sources. Plants were supplied with inorganic (dibasic sodium phosphate) and organic P sources (phytate and glucose phosphate) at three concentrations and grown for 40 d under sterile conditions. Three inoculation treatments were compared: control (non-inoculated plants), inoculation with Bacillus amyloliquefaciens BNM340, and inoculation with Pseudomonas fluorescens BNM296 (two bacteria with proven phytase activity). Oilseed rape, sunflower and soybean could utilize organic P sources. For example, when phytate (0.5 mM) P was used as the external P source, the increase factors over the no-P treatments were 4.5, 1.4, and 1.4 for oilseed rape, sunflower, and soybean P uptake, respectively. When glucose 1-phosphate disodium salt (G1P, 0.5 mM) was the P source, the increase factors were 8.8, 1.7, and 1.9 respectively. Positive responses to the organic P sources were found for the biomass accumulation of oilseed rape and soybean but not for sunflower. The inoculation with bacteria did not exert a promoting effect on P uptake. We demonstrate that the three species can effectively use organic P sources. The existence of crop plants that are more efficient in the utilization of different soil P sources would be particularly beneficial to improve P recycling and use of P fertilizers in agriculture.